Annex 1: description of action - Inter-American Institute for Cooperation on Agriculture, Asociación de Cultivadores de Banano (BGA) (Belice) (2019)
This project is developed within the context of the Banana Accompanying Measures (BAM) 2013 program to provide financial assistance to the Belize banana sector, more specifically the Banana Growers Association (BGA) and the University of Belize (UB). It aims in delivering practices to address soil fertility problems in order to improve the efficiency of banana production and to enhance the capacity of the University of Belize micropropagation laboratory for improved production of banana meristems.